Food shortages and hunger as a global problem - GONCHAROVA,Nadezhda Anatolyevna (2022)
Abstract The gist of this article boils down to the study of the food problem as a global problem of the modern economy. The food problem cannot be tackled in isolation from other complex global challenges facing humankind. At present, there is no state in the world in which the production, distribution, and foreign trade in foodstuffs would not be a serious concern of the central authorities. And in this respect, the problem under consideration also acts as a planetary one, despite the fact that some countries are faced with a chronic lack of food, in others, the current goal has become a qualitative improvement in the diet in order to bring it closer to scientifically grounded norms, and some are even forced “to fight” with the surplus of manufactured products and diseases of the population caused by their excessive consumption. Only those countries that are actively reforming and modernizing their agriculture have achieved success in the fight against hunger and poverty. A methodical approach to the food problem is being developed; it is possible to cope with the problem of hunger. Depending on the value of the hunger index, three basic strategies are proposed to combat the food problem. The final positioning concept is formulated in the paper.